Animals and the Shaping of Modern Medicine One Health and its Histories - Woods, Abigail (Medicine and Biomedical Sciences in Modern History, 2018)
This book is open access under a CC BY 4.0 license. This book breaks new ground by situating animals and their diseases at the very heart of modern medicine. In demonstrating their historical significance as subjects and shapers of medicine, it offers important insights into past animal lives, and reveals that what we think of as 'human' medicine was in fact deeply zoological. Each chapter analyses an important episode in which animals changed and were changed by medicine. Ranging across the animal inhabitants of Britain's zoos, sick sheep on Scottish farms, unproductive livestock in developing countries, and the tapeworms of California and Beirut, they illuminate the multi-species dimensions of modern medicine and its rich historical connections with biology, zoology, agriculture and veterinary medicine. The modern movement for One Health - whose history is also analyzed - is therefore revealed as just the latest attempt to improve health by working across species and disciplines. This book will appeal to historians of animals, science and medicine, to those involved in the promotion and practice of One Health today.